2020
DOI: 10.3390/molecules25163597
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Lattice Response to Hydrogen Absorption in Thin Pd and CoPd Films

Abstract: Hydrogen can penetrate reversibly a number of metals, occupy the interstitial sites and cause large expansion of the crystal lattice. The question discussed here is whether the kinetics of the structural response matches hydrogen absorption. We show that thin Pd and CoPd films exposed to a relatively rich hydrogen atmosphere (4% H2) inflate irreversibly, demonstrate the controllable shape memory, and duration of the process can be of orders of magnitude longer than hydrogen absorption. The dynamics of the out-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It is noteworthy that Pd–Sn NTs exhibited low limit of detection (LOD) values of 1 ppm; although the Pd–Sn NTs show a very low signal-to-noise ratio at extremely low concentrations of hydrogen, it is very clearly displayed in Figure a that the alloying with Sn and the formation of hollow porous nanostructure have substantially improved the detection limit as well as the signal-to-noise ratio compared to that of Pd NFs in Figure S6. Interestingly, the electrical resistances of sensors quickly increased once exposed to H 2 with concentrations above 500 ppm, as shown in Figure c,d, following the standard gas sensing characteristics of Pd-based H 2 sensors ( R gas – R air > 0). , These different behaviors of resistance change can be explained by the switchable H 2 sensing mechanisms at different H 2 concentrations. When exposed to H 2 with concentrations below 0.02%, the resistance is mainly influenced by two parameters as follows: first, the dissociated H atoms diffused into the Pd lattice and induced the formation of α-PdH x , leading to lattice expansion (HILE effect) and subsequent volume change which closes the grain interfaces and gaps to create more conductive channels.…”
Section: Results and Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It is noteworthy that Pd–Sn NTs exhibited low limit of detection (LOD) values of 1 ppm; although the Pd–Sn NTs show a very low signal-to-noise ratio at extremely low concentrations of hydrogen, it is very clearly displayed in Figure a that the alloying with Sn and the formation of hollow porous nanostructure have substantially improved the detection limit as well as the signal-to-noise ratio compared to that of Pd NFs in Figure S6. Interestingly, the electrical resistances of sensors quickly increased once exposed to H 2 with concentrations above 500 ppm, as shown in Figure c,d, following the standard gas sensing characteristics of Pd-based H 2 sensors ( R gas – R air > 0). , These different behaviors of resistance change can be explained by the switchable H 2 sensing mechanisms at different H 2 concentrations. When exposed to H 2 with concentrations below 0.02%, the resistance is mainly influenced by two parameters as follows: first, the dissociated H atoms diffused into the Pd lattice and induced the formation of α-PdH x , leading to lattice expansion (HILE effect) and subsequent volume change which closes the grain interfaces and gaps to create more conductive channels.…”
Section: Results and Discussionmentioning
confidence: 60%
“…Interestingly, the electrical resistances of sensors quickly increased once exposed to H 2 with concentrations above 500 ppm, as shown in Figure 4c,d, following the standard gas sensing characteristics of Pd-based H 2 sensors (R gas − R air > 0). 39,40 4f, the sensitivity was shown to increase linearly with the H 2 concentration, following the observed resistance change behaviors. In addition, Figure S8 illustrated the normalized sensitivity of the four sensors (Pd−Sn NTs, Pd−Sn NFs, Sn NFs, and Pd NFs) to H 2 with concentrations ranging from 1% to 3%, where the sensitivity of Pd NFs behaved abnormally at 3% H 2 and was accompanied by an increase of baseline resistance.…”
Section: Resultsmentioning
confidence: 66%
“…Hydrogen diffusion and the hydride formation accelerates with an increasing Co content down to a few sec in Co 40 Pd 60 [ 40 ], which is quicker than in pure Pd. An enhanced diffusivity rate in these strongly diluted Pd-Co films is consistent with the conclusions of earlier studies of Pd-Au and Pd-Ag membranes [ 46 , 47 ] and Au-alloyed Pd surfaces [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…As was demonstrated in Ref. [ 40 ], the time dependence of the hydride scattering term can differ significantly from the lattice response one. It was suggested that loading the metal host with a large amount of hydrogen can create an out-of-equilibrium state.…”
Section: Introductionmentioning
confidence: 90%
“…Density functional theory (DFT) is a well-established computational approach in material science, physics, and chemistry for the prediction of physical and chemical properties. DFT has been used to study numerous metal–hydrogen systems across the periodic table, including palladium alloys, titanium, and many other systems. It has also been used to compute bulk absorption in plutonium as well as hydrogen ML coverage on its low-energy facets .…”
Section: Introductionmentioning
confidence: 99%